Vocabulary Learning Strategies in EFL Classes: Perspectives and Challenges - Rezhna Ibrahim Ali; Anjumen Muhammad Sabir; Qismat Mohammad Hussein (Zanco Journal of Humanity Sciences)
This study aims to find out (a) which vocabulary learning Strategy (VLS) is used by Kurdish EFL learners in their learning processes the most and the least, (b) the perceptions of Kurdish EFL teachers towards VLS, (c) the challenges that are encountered by teachers while teaching vocabulary. Forty (40) undergraduate second year students from Salahaddin University/College of Basic Education and fifteen (15) EFL teachers participated in the study.  A mixed method of data were gathered through the use of a VLS questionnaire and a semi-structured interview. A closed-ended questionnaire was adapted from Schmitt’s Vocabulary Learning Strategies Taxonomy (1997). The results showed that the most frequently used strategy was determination, followed by Metacognitive, Memory, Social, and Cognitive as the least frequently applied by the Kurdish EFL students. Teachers reported that vocabulary plays a significant role in language learning; they use these strategies sub-consciously, and the most common challenges in teaching vocabularies include: mispronunciation, misspelling, misuse of words, large classes and shyness of students.